Effect of hospital volume on outcomes of percutaneous peripheral atherectomy – An observational analysis from National Inpatient Sample. (December 2018) - Patel, Samir V; Sonani, Rajesh; Patel, Palak; Patel, Mihir; Bhatt, Parth; Badheka, Apurva
Background: Although the published literature has reported an inverse association between hospital volume and outcomes of coronary interventions, sparse data are available for percutaneous peripheral atherectomy (PPA). The aim of our study was to examine the effect of hospital volume on outcomes of PPA. Methods: Using the Nationwide Inpatient Sample (NIS) database of the year 2012, PPA with ICD-9 code of 17.56 was identified. The primary outcomes were mortality and amputation rates; secondary outcomes were peri-procedural complications, cost, and length of hospitalization and discharge disposition of the patient. Multivariate models were generated for predictors of the outcomes. Results: We identified a total of 21, 015 patients with mean age of 69.53 years, with 56% males. Higher hospital volume centers were associated with a significantly lower mortality (OR 0.42, 95% CI 0.30–0.57, p < 0.0001), amputation rates (5.34% vs. 9.32%, p < 0.0001), combined endpoint of mortality and complications (OR 0.53, 95% CI 0.49–0.58, p < 0.0001), shorter length of hospital stay (LOS) (4.86 vs. 6.79 days, p < 0.0001) and lower hospitalization cost (23, 062 vs. 30, 794, p < 0.0001). Subgroup analysis for acute and chronic limb ischemia showed similar results. Conclusion: Hospital procedure volume is an independent predictor of mortality, amputation rates, complications, LOS, and costs in patients undergoing PPA with an inverse relationship.